IDENTIFIKASI SIFAT FISIK TANAH ALIH FUNGSI LAHAN HUTAN MENJADI PERKEBUNAN KAKAO(Theobroma cacao L.) DI DESAPARIGIMPU’UKECAMATAN PARIGI BARAT KABUPATEN PARIGI MOUTONG - Sutrisno Jasmin; Ramlan Ramlan; Anthon Monde (Universitas Tadulako, 2017)
This study aimed to determine the physical properties of the soil under forest land and that under forest land converted into plantations of cacao (Theobroma cacao L.) in Parigimpu'uvillage, West Parigi sub district, ParigiMoutong district. Soil analysis was carried out in the Laboratory of Soil Science of the Faculty of Agriculture, TadulakoUniversity. Survey method used in this research was through observing and determining the research location. Three undisturbed and three disturbed soil samples were collected from each land use (forest and cacao plantation). The undisturbed soil samples were taken from 0 – 20 cm soil depth using soil rings while the disturbed soil sample were obtained compositely from the same depth. The research results showed that the soil characteristics in the cacao plantation tended to decreased compared to that in the forest land. Soil bulk density ranged from light to heavy with porosity varied from less to good. Soil texture was dominated by sand fractions in the forest land with relatively lowsoil C-organic.